2022
DOI: 10.1002/jad.12094
|View full text |Cite
|
Sign up to set email alerts
|

A multimethod examination of hope and adolescent STEM career expectancies

Abstract: Introduction: Science, technology, engineering, and mathematics (STEM) fields are growing rapidly and understanding adolescent's interest and hope for pursuing a STEM career is essential for additional growth and opportunity collectively and individually. Hope is a cognitive-motivational construct that includes three components: hopeful future expectations (HFEs), intentional self-regulation (ISR), and connection, and is associated with academic achievement and career pursuit; it has not been examined in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Previous literature has reported that those who have hopes for STEM elds have higher motivation (Eccles & Wang, 2016). Alexander et al (2022) concluded that STEM hope is effective in uncovering students' full potential in STEM elds. Therefore, it seems obvious that STEM hope predicts STEM career aspirations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has reported that those who have hopes for STEM elds have higher motivation (Eccles & Wang, 2016). Alexander et al (2022) concluded that STEM hope is effective in uncovering students' full potential in STEM elds. Therefore, it seems obvious that STEM hope predicts STEM career aspirations.…”
Section: Discussionmentioning
confidence: 99%